Financial Literacy. A Case Study in Madiun - Halleina Rejeki Putri Hartono; Yopie Diondy Kurniawan; La Ode Abdullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial literacy is very important (Chhow & Ansong, 2010) for young people. This can form a habit of saving and accumulating assets for young people. Financial literacy is also the key (Ansong & Gyensare, 2012) to reduce financial problems, especially for young adults. Financial literacy (Shaari, Hasan, Mohamed, & Sabri, 2013) can also prevent young people from overusing third party funds. This financial literacy can influence decision making regarding financial problems in young people. The literacy level assessment carried out on young people will provide insight for researchers in understanding behavior related to finance.This study uses a quantitative method approach. The data source used is Madiun City youth in the age range of 18-39 years. The data collection technique used is to use a questionnaire or questionnaire. The results show that the financial literacy of young people in Madiun City is at a low level.